North Carolina Winegrowers' Perceptions of Climate Change Impacts - Blair, Heather (East Carolina University, 2013)
Wine is a product of a specific region’s climate and environment. Climate change is a source of increasing sensitivity. This research analyzes the perceptions of winegrape growers and climate trends, which contribute to a better understanding of climate change impacts on winegrape production and adaptation strategies. Results are compiled from 12 winegrower interviews and 34 web survey responses to questions on crop sensitivity to potential changes in climate as well as current experiences and adaptations to perceived changes to discover how climate change is affecting this sector of agriculture within North Carolina’s distinct climate environments. Web survey and interview responses specify weather and climate as a very strong element of risk. Excessive rainfall, hail, severe weather and late spring frosts are among the greatest threats varying between regions and variety. Almost all respondents indicate experiencing a change in extreme high temperatures. The majority of respondents who indicated any concern for future climate change explained preparations are in place because there is no control over the weather, only adaptation. Climate patterns and trends are analyzed for the period 1982-2012, showing the southern mountain region is experiencing a slight increase in August mean maximum temperatures. Temperature trend lines suggest that the central region of the state is experiencing an overall increase in January mean minimum temperature. Boundaries suitable for specific varieties have changed as increasing temperatures expand zones of disease risk.
Keywords: Geography; Agriculture; Climate changes; Adaptation; North Carolina; Risk; Suitability; Climatic changes--Environmental aspects--North Carolina; Viticulture--North Carolina; Viticulturists--North Carolina